Corrosion and Corrosion Inhibition of α-Brass by Thiourea - Aziz Isa, Wisal Abdil; Ahmed, Awf A.R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The corrosion behavior and corrosion inhibition of α-brass (65.3% Cu, 34.4% Zn and others 0.3%) in 0.6 mol.dm-3 NaCl solution have been investigated using potentiostatic polarization technique, the main results obtained were expressed in terms of corrosion (Ec) and corrosion current (ic). The research was performed in neutral and slightly acidic media [pH=7 and pH=4] over the temperature range (288-318)K. It was found that the rate of corrosion increases with the increase of acidity and the increase of temperature. The rate of corrosion increased with the increase of temperature in conformity with Arrhenius equation. Values of activation energy (Ea*), pre-exponential factor (A) and entropy of activation (∆S*) have been derived for the corrosion process. Also the thermodynamic quantities (∆G, ∆S and ∆H) have been determined for the process. The inhibition effect of thiourea on the corrosion of α-brass in chloride solution was studied, and it was found that the addition of thiourea to the chloride solution caused a decrease in the values of corrosion current density and changed to some extent the values of kinetic parameters. The values of (Ea) increases in the presence of thiourea, this means that the decrease of the concentration of thiourea